Clinical study on the treatment of subluxation of the small joint of the cervical vertebrae by acupuncture plus Tuina - Yu-ying, Sun; Ming-ming, Feng (Journal of acupuncture and tuina science, 2004)
To observe the clinical therapeutic effect of the subluxation of the small joints of the cervical vertebrae by acupuncture plus Tuina, 178 subjects were divided randomly into acupuncture group, Tuina group and acupuncture plus Tuina group to receive the corresponding treatment. The cure rate in acupuncture plus Tuina was 68.8%, which is higher than that in acupuncture group (27.8%) and that in Tuina group (28.6%) and the statistical management showed significant differences. Acupuncture combined with Tuina could enhance the therapeutic effect in the treatment of the subluxation of the small joints of the cervical vertebrae.